Cyclobutane dication, (CH2)42+: a model for a two-electron four-center (2e-4c) Woodward–Hoffmann frozen transition state - Prakash, G. K. Surya; Rasul, Golam (Beilstein Journal of Organic Chemistry, 2019)
The structures of the elusive cyclobutane dication, (CH2)42+, were investigated at the MP2/cc-pVTZ and CCSD(T)/cc-pVTZ levels. Calculations show that the two-electron four-center (2e-4c) bonded structure 1 involving four carbon atoms is a minimum. The structure contains formally two tetracoordinate and two pentacoordinate carbons. The non-classical σ-delocalized structure can be considered as a prototype for a 2e-4c Woodward–Hoffmann frozen transition state. The planar rectangular shaped structure 2 with a 2e-4c bond was found not to be a minimum.
Keywords: cyclobutane dication; 2e-4c bond; frozen transition state; Woodward–Hoffmann rule